Invariants of vector configurations - Andrew Berget; Alex Fink (Discrete Mathematics & Theoretical Computer Science, 2012)
We investigate the Zariski closure of the projective equivalence class of a matrix. New results are presented regarding the matrices in this variety and their matroids, and we give equations for the variety. We also discuss the K-polynomial of the closure of a projective equivalence class, and two other geometric invariants that can be obtained from this.